Ensiling Characteristics and the Nutrient Degradability of a By-product Feed-based Silage - Y. I. Kim; Y. K. Oh; K. K. Park; W. S. Kwak (Asian-Australasian Journal of Animal Sciences, 2014)
This study was conducted to evaluate the ensiling characteristics and the in situ degradability of a by-product feed (BF)-based silage. Before ensilation, the BF-based mixture was composed of 50% spent mushroom substrate, 21% recycled poultry bedding, 15% ryegrass straw, 10.8% rice bran, 2% molasses, 0.6% bentonite, and 0.6% microbial inoculant on a wet basis and ensiled for up to 4 weeks. The BF-based silage contained on average 39.3% moisture, 13.4% crude protein (CP), and 52.2% neutral detergent fiber (NDF), 49% total digestible nutrient, and 37.8% physically effective NDF1.18 on a dry matter (DM) basis. Ensiling the BF-based silage for up to 4 weeks affected (p<0.01) the chemical composition to a small extent, increased (p<0.05) the lactic acid and NH3-N content, and decreased (p<0.05) both the total bacterial and lactic acid bacterial counts from 109 to 108 cfu/g when compared to that before ensiling. These parameters indicated that the silage was fermented and stored well during the 4-week ensiling period. Compared with rice or ryegrass straws, the BF-based silage had a higher (p<0.05) water-soluble and filterable fraction, a lower insoluble degradable DM and CP fraction (p<0.05), a lower digestible NDF (p<0.05) fraction, a higher (p<0.05) DM and CP disappearance and degradability rate, and a lower (p<0.05) NDF disappearance and degradability rate. These results indicated that cheap, good-quality BF-based roughage could be produced by ensiling SMS, RPB, rice bran, and a minimal amount of straw.